2003
DOI: 10.1002/anie.200352399
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Aryl Halosilanes through Iridium(I)‐Catalyzed Aromatic CH Silylation by Disilanes

Abstract: Aryl halosilanes and their hypervalent derivatives are versatile reagents for carbon-carbon [1][2] and carbon-heteroatom [3] bond formation in modern organic synthesis. Although they have been prepared by arylation of halosilanes with aryl magnesium or aryl lithium reagents, [4] and by Pd-catalyzed cross-coupling of halogenated disilanes with aryl electrophiles, [5] direct silylation of arenes through C À H bond activation would provide a more attractive route from the viewpoints of economy, efficiency, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 30 publications
0
35
1
2
Order By: Relevance
“…Furthermore, the removal of alkyl masking groups in the presence of silanes is not trivial. Miyaura 18 and Hartwig 19 have reported Rh- and Ir-catalyzed steric-controlled meta- or para- silylation of anisoles, respectively (Scheme 1.a2). Whereas Miyaura’s Ir-catalyzed silylation required 60-fold excess of anisole substrates 5 , the method developed by Hartwig showed broad substrate scope and high site-selectivity, yet the removal of a hydroxyl masking group in the presence of silanes is again questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the removal of alkyl masking groups in the presence of silanes is not trivial. Miyaura 18 and Hartwig 19 have reported Rh- and Ir-catalyzed steric-controlled meta- or para- silylation of anisoles, respectively (Scheme 1.a2). Whereas Miyaura’s Ir-catalyzed silylation required 60-fold excess of anisole substrates 5 , the method developed by Hartwig showed broad substrate scope and high site-selectivity, yet the removal of a hydroxyl masking group in the presence of silanes is again questionable.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such limitations, perhaps a more practical approach is to first install a latent FG site selectively through C−H activation and then branch out to other FGs through reliable chemistry. For instance, C−H borylation [18][19][20][21][22] , silylation 18,23,24 and fluorination 25 of arenes serve as seminal examples of diverse functionalizations of an sp 2 C−H bond through the transformations of aromatic boranes, silanes and fluorides. In contrast, for unactivated (for example, non-benzylic, -allylic, -α to a heteroatom or -strained) sp 3 C−H bonds, although the corresponding C−H borylation and silylation have been demonstrated elegantly 18,[26][27][28][29][30][31] , the diversification becomes more challenging because of the significantly reduced reactivity of alkyl boranes and silanes towards electrophiles 32 .…”
mentioning
confidence: 99%
“…[13] We found that the arylation between 1 a and o-xylene (2 a) took place smoothly in the presence of Pd(OAc) 2 (10 mol %) as a catalyst with Cu(OTf) 2 (20 mol %) as an oxidative cocatalyst [Eq. [14] To further verify our prediction, the more sterically hindered p-xylene was subjected to this transformation, and ortho arylation was observed in very low yield, with most of the starting material 1 a being recovered. Gratifyingly, dioxygen (O 2 , 1 atm) could be applied as the terminal oxidant to complete this transformation.…”
Section: Multiple C à H Activations To Construct Biologically Active mentioning
confidence: 71%
“…In the proposed mechanism (Scheme 2), the selectivity in this arylation was most likely controlled by the acetamino directing group in the first CÀH activation [13] and by steric effects in the second CÀH activation. [14] To further verify our prediction, the more sterically hindered p-xylene was subjected to this transformation, and ortho arylation was observed in very low yield, with most of the starting material 1 a being recovered.…”
mentioning
confidence: 71%